Pengaruh Media Gambar Terhadap Penguasaan Mufrodat Siswa MTs Islamiyah Banat Senori Tuban - Habib Abdul Halim (Jurnal Pendidikan Bahasa Arab, 2024)
Image media is one of the Arabic language teaching methods that is used to convey and facilitate Arabic language subjects, and because vocabulary is one of the elements of the language, and this is where Arabic is. Therefore, understanding vocabulary is very important in teaching foreign languages, meaning Arabic. In this scientific research entitled "The Influence of Image Media on the Vocabulary Understanding of Class VII Female Students at Islamic Middle School Putri Gatsari Snorri Tuban." The research problems are: 1) Is image media effective for understanding vocabulary for class VII students at SMP Islam Gatsari Snorri Tuban? 2) To what extent is the influence of image media on the vocabulary understanding of class VII students at SMP Islam Gatsari Snorri Tuban? The approach used in this research is a quantitative approach, namely research based on percentages, census calculations, etc., and the type is pre-post experimental without a separate control group. The research tool is: tests. Researchers obtained results from these calculations. The results of the average scale and the results of the t test using SPSS are Paired Samples Test and Model Summary, which means to determine the influence and extent of the size of image media on vocabulary understanding. For class VII students at SMP Islam Gatsari Snorri Tuban, we continue the value from 28 = 2.048, and the data analysis value is 5.716. So if we compare it, it is known that the t-test obtained is 5.716 > 2.048, meaning that teaching Arabic using picture media is effective for understanding vocabulary, and the effect is 30%.